(untitled) (Research, Society and Development, 2023)
The objective of this study was to evaluate the use and effectiveness of botulinum toxin for the decline of symptoms that this dysfunction causes, through a case report of a patient with TMD in which two applications of botulinum toxin type A were performed by a qualified dental surgeon, clinical exams based on the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) before the application and a 45-day follow-up after the first application to verify the result. It was verified that the action of Botulinum Toxins Type A (TXB-A) on the masseter and temporalis muscles significantly reduced the patient’s symptoms right after the first application. In the second, only the masseter muscle received the toxin because it was still in pain. With the follow-up using the RDC/TMD, it was possible to verify the decay of the muscular symptoms, remaining only the joint TMD. Botulinum toxin type A is not a treatment of choice due to the controversies surrounding its use as a therapy, but rather an adjuvant treatment for the muscular symptoms of TMD, requiring further studies to assess the long-term result and, also, that the patient continues multidisciplinary treatments to take care of his/her TMD.